Pemanfaatan Data Analitik dalam Big Data: Studi Kasus Implementasi di Pemerintahan - Hilabi, Shofa Shofiah; Savina, Savina; Khairunisa, Sabnabila (Universitas Multi Data Palembang, 2025)
This study examines the use of Big Data in public health management in Indonesia, with a special emphasis on the opportunities, problems, and impacts of using evidence-based data on decision-making. This research was conducted using a descriptive qualitative approach, which involved the analysis of secondary data from a number of relevant journal articles. The results of the study show that big data improves health policy, decision-making processes, and understanding of public health trends. Examples of practices that occurred during the COVID-19 pandemic show how big data analytics helps governments monitor vaccine deployment and distribution in real time. However, major issues such as lack of technological infrastructure, limited human resources, and data privacy issues continue to emerge. Research shows that with strengthened technology infrastructure, employee training, and better data security policies, the implementation of Big Data has great potential to improve the efficiency of public health management. According to this study, investment in information technology must be made, and also a policy framework that supports data integration between government agencies must be created.